Evaluation of the Airport Operational Performance Assessment System: Integration of Balanced Scorecard, AHP, and OMAX in the Halim Perdanakusumah Operations Services Division - Danang Brahmantyo S; Susetya Nugroho; Cedaryana Cedaryana (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to evaluate the operational performance appraisal system in the Perdanakusumah International Airport Operations Service Division and to analyze the integration of the Balanced Scorecard, Analytic Hierarchy Process, and Objective Matrix methods as a strategic performance evaluation model. The research employs a qualitative descriptive approach through observation, documentation studies, and analysis of operational performance indicators. The findings indicate that the existing appraisal system remains largely dominated by supervisor subjectivity, administrative indicators, and periodic manual evaluations that do not support real-time operational performance monitoring. The study identifies gaps in terms of transparency, strategic relevance, and the effectiveness of operational performance measurement. To address these issues, this research proposes an integrated model combining the Balanced Scorecard, AHP, and OMAX to enhance assessment objectivity, KPI prioritization, and operational performance monitoring. This integrated model enables the organization to align individual performance with airport strategic targets, improve monitoring accuracy, and support the development of a digital-based performance management system. This study contributes to the advancement of strategic performance management systems within the airport operational service sector.